Carotid atherosclerosis: An independent risk factor for small fiber nerve dysfunction in patients with type 2 diabetes mellitus. Issue 2 (9th November 2022) - Guo, Simin; Jing, Yali; Li, Chenxi; Zhu, Dalong; Wang, Weimin
Abstract: Aims/Introduction: To explore whether carotid atherosclerosis is an independent risk factor for small fiber nerve dysfunction in type 2 diabetes mellitus patients. Materials and Methods: A total of 247 type 2 diabetes patients from Nanjing Drum Tower Hospital received carotid ultrasonography and quantitative sensory testing, including cold and warm detection thresholds, and some patients received cold and heat pain detection thresholds, respectively. According to the results of quantitative sensory testing, patients were divided into normal small fiber nerve function (NSF) and small fiber nerve dysfunction (SFD) group. Meanwhile, patients were divided into the non‐carotid atherosclerosis group, carotid intimal thickening, unilateral carotid atherosclerosis and bilateral carotid atherosclerosis group. The correlation between carotid ultrasonography with quantitative sensory testing parameters was analyzed by SPSS 26.0. Results: First, the incidence rate of SFD increased significantly in patients with carotid atherosclerosis (72.2%, P  < 0.001) especially in bilateral carotid atherosclerosis (81.7%, P  < 0.001). Second, compared with the NS group, the carotid intima‐media thickness in SFD was thicker ( P  = 0.018) and the size of atherosclerotic plaque was larger ( P  < 0.001). In addition, the cold detection threshold decreased ( P  < 0.001), whereas the warm detection threshold ( P  < 0.001) and heat pain detection threshold ( P  < 0.001) increased as aggravation of carotid atherosclerosis . In the correlation analysis, the size of atherosclerotic plaque presented a positive correlation with the warm detection threshold ( r  = 0.476, P  < 0.001) and heat pain detection threshold ( r  = 0.213, P  < 0.001), but presented a negative correlation with the cold detection threshold ( r  = −0.239, P  < 0.01). Furthermore, carotid atherosclerosis (odds ratio 2.326, P  = 0.017), especially bilateral carotid atherosclerosis (odds ratio 5.042, P  = 0.001), was an independent risk factor for SFD ( P  < 0.05). Conclusions: Carotid atherosclerosis was significantly associated with quantitative sensory testing and found to be an independent risk factor for small fiber nerve dysfunction in type 2 diabetes patients. Abstract : In this study, a total of 247 T2DM patients were enrolled and they all received carotid ultrasonography and quantitative sensory testing which indicates the function of small fiber nerve. And the correlation between these two parameters were analyzed by SPSS 26.0. Finally, we found that carotid atherosclerosis was significantly associated with quantitative sensory testing and found to be an independent risk factor for small fiber nerve damaging in T2DM. This study is benefit to the prevention and early diagnosis of diabetes complication especially small fiber neuropathy.